USP5 Suppresses Ferroptosis in Bladder Cancer Through Stabilization of GPX4 - Caiying Liu; Yanong Deng; Liang Huang; Xinrui Nie; Yuxuan Jiang; Xia Zhang; Huihui Zhang (Current Issues in Molecular Biology)
USP5 has been proven to play an important role in the proliferation of bladder cancer (BC). In this study, we focused on investigating the molecular mechanism of ferroptosis induced by USP5 in bladder cancer. The role of USP5 in bladder cancer was evaluated using T24 wild-type cells (WT) and USP5 knockout (USP5−/−) by CCK8 and colony formation assays. The contents of ferrobivalent ions (Fe2+), reactive oxygen species (ROS), and malondialdehyde (MDA) were detected using a determination kit to observe the relationship between USP5 and ferroptosis. Furthermore, the molecular mechanism study was evaluated by employing Western blotting, co-immunoprecipitation, RT-qPCR, ubiquitination assays, etc. This study showed genetic ablation of USP5 significantly inhibited the viability and proliferation of bladder cancer cells. Genetic ablation of USP5 promoted increases in Fe2+ content, ROS, and MDA levels. The addition of erastin significantly increased the viability and proliferation of T24 USP5−/− cells and significantly increased their ROS and MDA contents. We verified that USP5 deficiency led to a significant reduction in GPX4 protein levels and that the overexpression of USP5 could stabilize the GPX4 protein. Further studies showed that USP5 interacts with GPX4 and stabilizes GPX4 by inhibiting its ubiquitination These findings revealed USP5 inhibits ferroptosis in bladder cancer cells by stabilizing GPX4. The relationship between USP5 and ferroptosis could be a potential therapeutic target for bladder cancer.